A modified ultrafiltration membrane for solid-liquid separation of a system containing suspended particles, a preparation method and application thereof

CN122998992APending Publication Date: 2026-10-30XINZHUANG COAL MINE OF QINGYANG XINZHUANG COAL IND CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611155791.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]基于上述技术缺陷,本发明的目的在于克服现有技术中硫酸根去除分离效率低、药剂昂贵、钙矾石沉淀固液分离时间长、常规膜在强碱环境下易腐蚀等问题,本发明提供一种用于含悬浮颗粒体系固液分离的改性超滤膜及其制备方法和应用

Benefits of technology

1、本发明通过将钙矾石化学沉淀与改性膜错流过滤相耦合,固液分离时间从传统重力沉降的数小时缩短至分钟级,处理效率提升10倍以上,设备占地面积显著减小。本发明的改性膜表面构建的植酸-锆离子-聚乙烯亚胺氢键-配位双重交联网络具有珍珠层仿生结构。植酸的6个磷酸基团提供超高密度水合位点,使膜表面水接触角降至25~35°,形成致密水合层,通过空间位阻效应有效阻止钙矾石颗粒及溶解性离子靠近膜表面;Zr4+在强碱环境中不沉淀,反而与植酸形成稳定的Zr-O-P配位网络,同时生成Zr-O-Zr氧桥结构,显著增强改性层的化学稳定性和耐碱腐蚀能力;通过多巴胺氧化自聚合在PEK-OH表面形成富含儿茶酚基团和氨基的中间层。该层一方面与PEK-OH形成共价键和氢键,另一方面与上层PA-Zr4+-PEI功能层形成氢键、配位键和π-π堆叠作用,实现“共价键+氢键+配位键+π-π堆叠”的四重界面结合。此外,PDA的儿茶酚基团对钙矾石颗粒表面的Ca²+具有特异性螯合作用,在膜表面形成局域正电荷富集层,对带负电的钙矾石颗粒产生静电排斥,实现从“被动排斥”向“主动排斥”的跨越。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998992A_ABST
    Figure CN122998992A_ABST
Patent Text Reader

Abstract

The application relates to a modified ultrafiltration membrane for solid-liquid separation of a suspended particle-containing system and a preparation method and application thereof, in particular to the modified ultrafiltration membrane which comprises a polydopamine intermediate layer and a phytic acid-zirconium ion-polyethyleneimine functional layer in sequence; the polydopamine intermediate layer is combined on the surface of a polyether ketone-based membrane, and the phytic acid-zirconium ion-polyethyleneimine functional layer is combined on the surface of the polydopamine intermediate layer; the phytic acid-zirconium ion-polyethyleneimine functional layer comprises an inorganic layer formed by coordination and crosslinking of phytic acid and zirconium ions and an organic layer formed by hydrogen bond crosslinking of polyethyleneimine, and the inorganic layer and the organic layer are alternately arranged. The application can significantly inhibit adhesion of calcium aluminate particles and deposition of inorganic salt scale, and realizes efficient and stable treatment of high-sulfate mine water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of mine water treatment and membrane separation technology, specifically relating to a modified ultrafiltration membrane for solid-liquid separation of systems containing suspended particles, its preparation method, and its application. Background Technology

[0002] Coal and metal mining operations generate large quantities of highly mineralized mine water, with sulfate content reaching thousands or even tens of thousands of milligrams per liter. Direct discharge causes severe sulfate pollution, while reuse easily leads to calcium sulfate scale formation in downstream units such as reverse osmosis, resulting in equipment scaling and reduced efficiency. Among existing sulfate removal technologies, the calcium chloride method introduces chloride ion impurities, and calcium sulfate has high solubility, resulting in incomplete removal; the barium chloride method involves expensive reagents and uses hazardous chemicals, posing significant safety risks. In recent years, the ettringite precipitation method (Ca6Al2(OH)2) has emerged as a promising alternative. 12 (SO4)3·26H2O has attracted attention due to its extremely low solubility (pKsp=43.13) and high sulfate removal rate. However, ettringite precipitates are needle-shaped crystals with extremely poor settling performance, resulting in solid-liquid separation times of several hours, leading to long treatment cycles and large facility footprints. Existing technologies, such as Chinese patents CN104603068A and CN108793498A, use ettringite precipitation to treat sulfate-containing wastewater, but solid-liquid separation still relies on clarifier sedimentation or conventional filtration, which is inefficient, difficult to achieve rapid and continuous operation, and does not employ membrane separation technology for enhancement. Chinese patent CN109179743A uses flocculation sedimentation, magnetic flocculation sedimentation, and filtration, but the sedimentation unit still relies on gravity sedimentation, resulting in a long process chain, high equipment investment, and failure to solve the scaling and fouling problem faced by the membrane separation unit. In addition, the precipitation reaction of ettringite needs to be carried out under strongly alkaline conditions (pH 10.5~12.5). Conventional organic membranes are prone to performance degradation or corrosion under such conditions and cannot meet the requirements for long-term stable operation.

[0003] In summary, there is an urgent need in this field to develop a high-sulfate mine water treatment technology that can achieve deep removal of sulfate, rapid solid-liquid separation, and long-term anti-pollution performance. Summary of the Invention

[0004] Based on the aforementioned technical deficiencies, the purpose of this invention is to overcome the problems of low sulfate removal and separation efficiency, expensive reagents, long solid-liquid separation time for ettringite precipitation, and easy corrosion of conventional membranes in strongly alkaline environments in existing technologies. This invention provides a modified ultrafiltration membrane for solid-liquid separation in systems containing suspended particles, its preparation method, and its application. This application provides a method for generating ettringite precipitate based on calcium aluminate powder instead of aluminum and calcium sources, coupled with a specific "brick-mud" biomimetic structure, and the development of a "PEK base membrane—PDA intermediate layer—PA-Zr" structure. 4+A method for treating high-sulfate mine water using a three-layer gradient structure modified ultrafiltration membrane with a "PEI functional layer" is described, along with the modified membrane preparation process. This application significantly shortens the solid-liquid separation time through process coupling and addresses the unique surface charge characteristics and membrane fouling mechanism of ettringite needle-like crystals via PA-Zr... 4+ The specific combination and synergistic effect of PEI and other components construct a membrane surface functional layer that combines superhydrophilicity, strong charge shielding, and high structural stability, thereby significantly inhibiting the adhesion of ettringite particles and the deposition of inorganic salt scale, achieving efficient and stable treatment of high sulfate mine water.

[0005] The first inventive point of this invention is a modified ultrafiltration membrane for solid-liquid separation of systems containing suspended particles. The modified ultrafiltration membrane comprises, in sequence, a polyetherketone-based membrane, a polydopamine interlayer, and a phytic acid-zirconium ion-polyethyleneimine functional layer; the polydopamine interlayer is composited on the surface of the polyetherketone-based membrane, and the phytic acid-zirconium ion-polyethyleneimine functional layer is composited on the surface of the polydopamine interlayer. The phytic acid-zirconium ion-polyethyleneimine functional layer has a nacreous biomimetic structure formed by the interpenetration of an inorganic framework formed by the coordination and cross-linking of phytic acid and zirconium ions and an organic network formed by the cross-linking of polyethyleneimine through hydrogen bonds.

[0006] Furthermore, the modified ultrafiltration membrane has a water contact angle of 25~35° on its surface, and the modified ultrafiltration membrane is structurally stable in a strongly alkaline environment with a pH of 10.5~12.5.

[0007] Furthermore, the thickness of the polyetherketone-based film is 100-250 μm; the thickness of the polydopamine intermediate layer is 5-50 nm; and the thickness of the phytic acid-zirconium ion-polyethyleneimine functional layer is 50-200 nm.

[0008] Preferably, the surface of the polyetherketone-based film is subjected to surface hydroxylation activation treatment to form a surface-hydroxylated polyetherketone-based film.

[0009] Preferably, the molar ratio of phytic acid, zirconium ions and polyethyleneimine in the phytic acid-zirconium ion-polyethyleneimine functional layer is (1-3):1:(0.5-6).

[0010] Furthermore, the modified ultrafiltration membrane exhibits a flux recovery rate of ≥86% after chemical cleaning during cross-flow filtration.

[0011] The second inventive point of this invention is a method for preparing the modified ultrafiltration membrane described above for solid-liquid separation of systems containing suspended particles, comprising the following steps: S1: The polyetherketone-based membrane is selectively reduced and activated with sodium borohydride to obtain a hydroxylated polyetherketone-based membrane; S2: The hydroxylated polyetherketone-based membrane prepared in step S1 is immersed in a buffer solution containing dopamine and subjected to an oxidative self-polymerization reaction under alkaline conditions to form a polydopamine intermediate layer on the surface of the hydroxylated polyetherketone-based membrane, thereby obtaining a PEK-OH / PDA composite membrane. S3: Phytic acid and zirconium ions are pre-assembled to form a phytic acid-zirconium ion coordination complex solution; the PEK-OH / PDA composite membrane prepared in step S2 is immersed in the coordination complex solution, so that the coordination complex is anchored on the surface of the polydopamine intermediate layer. S4: Immerse the membrane treated in step S3 into a polyethyleneimine solution to allow polyethyleneimine and phytic acid to crosslink through hydrogen bonds, thereby constructing a nacreous biomimetic brick-mud structure. After heat treatment, the modified ultrafiltration membrane is obtained.

[0012] Further, in step S1, the surface hydroxylation activation treatment includes: immersing the polyether ketone-based film in concentrated sulfuric acid and treating it at 20~30°C for 5-8 min to perform sulfonation and pore formation, and then transferring it to a NaBH4 / DMSO solution and reacting it at 120°C for 4 h under N2 protection to selectively reduce the ketone groups on the surface of the polyether ketone-based film to hydroxyl groups.

[0013] Further, in step S2, the buffer solution is a Tris-HCl buffer solution with a pH of 8.0-9.0; the concentration of dopamine is 1-5 g / L; and the oxidative self-polymerization reaction is carried out at 25-40°C in the dark for 6-24 hours.

[0014] Further, in step S3, the molar ratio of phytic acid to zirconium ions is (1~3):1; the coordination pre-assembly is carried out at room temperature, and the pre-reaction time is 20~60 min; the PEK-OH / PDA composite membrane is immersed in the coordination complex solution for 1~4 h.

[0015] Further, in step S4, the polyethyleneimine is branched polyethyleneimine with a molecular weight of 10,000 to 70,000; the mass concentration of the polyethyleneimine solution is 1 to 5 wt%; the impregnation time is 15 to 60 min; and the heat treatment temperature is 50 to 80°C for 1 to 4 h.

[0016] The third inventive point of this invention is a method for treating high-sulfate mine water based on ettringite precipitation coupled with modified membrane separation. The modified ultrafiltration membrane described above is used for solid-liquid separation, and the method includes the following steps: A1: High-sulfate mine water is introduced into the ettringite reactor, and alkaline solution is added to adjust the pH to 10.5~12.5; A2: Add calcium aluminate powder to the ettringite reactor and react for 30-90 minutes under stirring to generate ettringite precipitate; A3: The reaction mixture containing calcite precipitate is fed into a membrane separation unit equipped with the modified ultrafiltration membrane, and solid-liquid separation is performed by cross-flow filtration. The permeate is collected as product water. A4: Adjust the pH of the produced water to neutral before reuse or discharge.

[0017] Further, in step A2, the dosage of calcium aluminate powder is 6.5~10.5 g / L, the stirring speed is 200~400 rpm, and the reaction temperature is 20~25°C; In step A3, the transmembrane pressure of the cross-flow filtration is 0.1~0.5 MPa, and the cross-flow velocity is 1.0~3.0 m / s; Furthermore, when the transmembrane pressure difference rises to 1.5 times the initial value, a chemical cleaning procedure is initiated: first, the membrane is washed with 0.5~1.0 wt% NaOH solution for 30~60 min, then with 0.2~0.5 wt% HCl solution for 30~60 min, and finally rinsed with deionized water until neutral; the flux recovery rate of the modified ultrafiltration membrane after chemical cleaning is ≥86%.

[0018] Furthermore, the solid-liquid separation time of the method is shortened from several hours by gravity sedimentation to minutes; the sulfate removal rate is ≥80%.

[0019] Beneficial effects 1. This invention couples ettringite chemical precipitation with modified membrane cross-flow filtration, reducing solid-liquid separation time from several hours in traditional gravity sedimentation to minutes, increasing treatment efficiency by more than 10 times, and significantly reducing equipment footprint. The modified membrane surface of this invention features a phytic acid-zirconium ion-polyethyleneimine hydrogen bond-coordination dual cross-linked network with a nacreous biomimetic structure. The six phosphate groups of phytic acid provide ultra-high density hydration sites, reducing the water contact angle on the membrane surface to 25-35°, forming a dense hydration layer. This effectively prevents ettringite particles and dissolved ions from approaching the membrane surface through steric hindrance; Zr 4+ It does not precipitate in a strongly alkaline environment; instead, it forms a stable Zr-OP coordination network with phytic acid, while simultaneously generating a Zr-O-Zr oxygen bridge structure, significantly enhancing the chemical stability and alkali corrosion resistance of the modified layer. Through dopamine oxidative self-polymerization, it forms an intermediate layer rich in catechol groups and amino groups on the PEK-OH surface. This layer forms covalent and hydrogen bonds with PEK-OH on one hand, and with the upper PA-Zr layer on the other. 4+ - The PEI functional layer forms hydrogen bonds, coordination bonds, and π-π stacking interactions, achieving a quadruple interfacial bond of "covalent bonds + hydrogen bonds + coordination bonds + π-π stacking". Furthermore, the catechol groups of PDA affect the Ca²⁺ oxidase on the surface of the ettringite particles.+ It has a specific chelating effect, forming a local positive charge enrichment layer on the membrane surface, which generates electrostatic repulsion against negatively charged ettringite particles, realizing the leap from "passive repulsion" to "active repulsion".

[0020] 2. The modified ultrafiltration membrane of this invention primarily resists fouling through the steric hindrance effect of the dense hydration layer of phosphate groups, while Zr 4+ Coordination crosslinking imparts structural stability to the coating. The dense hydration layer physically prevents ettringite particles and Ca²⁺ from spreading. + / SO4² - Ion pairs are located close to the membrane surface; a stable cross-linked network ensures that the modified layer does not detach or crack during long-term operation, thus maintaining durable antifouling performance. The above mechanisms work synergistically to fundamentally inhibit the adhesion of ettringite particles and the deposition of inorganic salt scale on the membrane surface.

[0021] 3. The total sulfate removal rate in this invention can reach over 80%. The ettringite precipitate can be dehydrated by pressure filtration and then utilized as a filling material or concrete expansion agent, among other building materials. Attached Figure Description

[0022] Figure 1 This is a process diagram for synthesizing calcium aluminum oxide powder; Figure 2 This is a process flow diagram of calcite coupling membrane technology; Figure 3 It is a pretreatment for surface activation of PEK base film; Figure 4 This is the PEK membrane modification process flow; Figure 5 This study investigates the effect of calcium aluminate powder dosage on sulfate removal rate. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this application clearer, a more detailed description is provided below. However, it should be understood that the description herein is merely for explaining this application and is not intended to limit its scope.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. All reagents and instruments used herein are commercially available, and the characterization methods involved can be found in relevant descriptions in the prior art, and will not be repeated here.

[0025] To further understand this application, the following detailed description is provided in conjunction with the preferred embodiments.

[0026] Example 1 This embodiment provides a modified ultrafiltration membrane for solid-liquid separation of a system containing suspended particles. The modified ultrafiltration membrane comprises, in sequence, a polyetherketone-based membrane, a polydopamine interlayer, and a phytic acid-zirconium ion-polyethyleneimine functional layer. The polydopamine interlayer is composited on the surface of the polyetherketone-based membrane, and the phytic acid-zirconium ion-polyethyleneimine functional layer is composited on the surface of the polydopamine interlayer. The phytic acid-zirconium ion-polyethyleneimine functional layer comprises an alternating arrangement of an inorganic layer formed by the coordination crosslinking of phytic acid and zirconium ions and an organic layer formed by the hydrogen bonding crosslinking of polyethyleneimine.

[0027] Polyetherketone (PEK) molecules contain rigid aromatic rings and ketone groups (C=O), endowing them with excellent chemical and thermal stability. After selective reduction with NaBH4, the surface ketone groups are converted to hydroxyl groups (-OH), providing covalent reaction sites for the chemical anchoring of PDAs. Simultaneously, PEK membranes can operate stably within a pH range of 2–14, solving the problem of "conventional membranes being intolerant to strong alkalis" in ettringite reaction systems (pH 10.5–12.5).

[0028] Dopamine undergoes oxidative self-polymerization under weakly alkaline and aerobic conditions to generate a polydopamine (PDA) layer rich in catechol groups (-catechol) and amino groups (-NH2). The catechol groups possess extremely strong adhesive properties, forming covalent bonds (ROC bonds) and hydrogen bonds (OH···O) with the hydroxyl groups on the PEK-OH surface. Simultaneously, π-π stacking occurs between the aromatic rings of the PDA and the aromatic rings of the phytic acid molecules. This quadruple interfacial bonding mechanism of "covalent bonds + hydrogen bonds + coordination bonds + π-π stacking" results in a bonding strength between the functional layer and the base film far exceeding that of traditional double crosslinking, making it difficult to peel off under cross-flow shear forces and alkaline conditions.

[0029] Phytic acid (PA) contains six phosphate groups (-PO4), which act as "building blocks" with Zr. 4+ Coordination crosslinking occurs to form a rigid inorganic network; PEI, acting as "mortar," forms NH···O=P hydrogen bonds with the phosphate hydroxyl groups of phytic acid through its abundant amino groups, connecting the inorganic brick layers one by one. The biomimetic structure with alternating organic and inorganic layers combines the rigidity of the inorganic layers with the toughness of the organic layers.

[0030] The catechin groups of PDA affect the Ca²⁺ on the surface of ettringite particles. + It exhibits specific chelating properties, forming a localized positive charge enrichment layer on the membrane surface, which electrostatically repels negatively charged ettringite particles (ζ-potential approximately -15 to -25 mV), i.e., "active repulsion." The phosphate groups of PA form strong hydrogen bonds with water molecules to construct a dense hydration layer, preventing particles from approaching due to steric hindrance, i.e., "passive repulsion." The combination of active and passive repulsion achieves an antifouling effect far exceeding that of a single mechanism.

[0031] As a further preferred embodiment, the modified ultrafiltration membrane has a water contact angle of 25~35° on its membrane surface, and the modified ultrafiltration membrane is structurally stable in a strongly alkaline environment with a pH value of 10.5~12.5.

[0032] Phytic acid contains six phosphate groups, each of which can form hydrogen bonds with multiple water molecules, creating an ultra-high-density hydration layer on the membrane surface. The catechol hydroxyl and amino groups in the PDA layer are also hydrophilic. The synergistic effect of these three layers significantly reduces the water contact angle on the membrane surface from ~92° of the original PEK membrane to 25~35°. The denser the hydration layer (the lower the contact angle), the more difficult it is for ettringite particles to break through the hydration layer and adhere to the membrane surface.

[0033] Zr 4+ It forms a Zr-OP coordination network with the phosphate groups of phytic acid, and further generates a Zr-O-Zr oxygen bridge structure in a strongly alkaline environment. This inorganic cross-linked network has extremely high chemical stability. The covalent anchoring of PDA and the multiple hydrogen bond cross-linking of PEI form an organic-inorganic hybrid interpenetrating network with the Zr-OP / Zr-O-Zr network, so that the entire functional layer does not undergo hydrolysis, swelling or desquamation under strongly alkaline conditions of pH 10.5~12.5.

[0034] As a further preferred embodiment, the thickness of the polyetherketone-based film is 100-250 μm; the thickness of the polydopamine interlayer is 5-50 nm; and the thickness of the phytic acid-zirconium ion-polyethyleneimine functional layer is 50-200 nm.

[0035] The thickness of the PDA layer is controlled between 5 and 50 nm. If it is too thin, it cannot provide enough anchoring points and π-π stacking effect; if it is too thick, it will block the micropores of the PEK base membrane, resulting in a decrease in membrane flux. This thickness range ensures that the PDA layer acts as an "anchoring agent" without sacrificing water permeability.

[0036] A synergistic balance is achieved in the functional layer thickness range of 50–200 nm: if it is too thin (<50 nm), the functional layer is incomplete, and part of the membrane surface is exposed to the pollutant environment; if it is too thick (>200 nm), the filtration resistance increases and the flux decreases. This thickness range ensures that the functional layer completely covers the membrane surface and exerts sufficient hydration repulsion and electrostatic repulsion effects, while not significantly increasing mass transfer resistance.

[0037] As a further preferred embodiment, the surface of the polyetherketone-based film is subjected to surface hydroxylation activation treatment to form a surface-hydroxylated polyetherketone-based film.

[0038] The ketone groups (C=O) on the surface of the PEK base film are chemically inert and difficult to form strong chemical bonds with the catechol groups of PDA. Selective reduction with NaBH4 converts the ketone groups (C=O) into hydroxyl groups (-OH), allowing the catechol groups of PDA to covalently bond with the hydroxyl groups (forming COC bonds). This is a prerequisite for achieving a strong interfacial bond between the PDA intermediate layer and the base film, and is also the basis for forming the "covalent bond" in the "quadruple interfacial bond".

[0039] As a further preferred embodiment, the molar ratio of phytic acid, zirconium ions and polyethyleneimine in the phytic acid-zirconium ion-polyethyleneimine functional layer is (1-3):1:(0.5-6).

[0040] As a further preferred embodiment, the modified ultrafiltration membrane exhibits a flux attenuation rate ≤30% during cross-flow filtration and a flux recovery rate ≥86% after chemical cleaning.

[0041] Example 2 This embodiment provides a method for preparing the modified ultrafiltration membrane for solid-liquid separation of systems containing suspended particles as described in Example 1, including the following steps: S1: The polyetherketone-based membrane is selectively reduced and activated with sodium borohydride to obtain a hydroxylated polyetherketone-based membrane; S2: The hydroxylated polyetherketone-based membrane prepared in step S1 is immersed in a buffer solution containing dopamine and subjected to an oxidative self-polymerization reaction under alkaline conditions to form a polydopamine intermediate layer on the surface of the hydroxylated polyetherketone-based membrane, thereby obtaining a PEK-OH / PDA composite membrane. S3: Phytic acid and zirconium ions are pre-assembled to form a phytic acid-zirconium ion coordination complex solution; the PEK-OH / PDA composite membrane prepared in step S2 is immersed in the coordination complex solution, so that the coordination complex is anchored on the surface of the polydopamine intermediate layer. S4: Immerse the membrane treated in step S3 into a polyethyleneimine solution to allow polyethyleneimine and phytic acid to crosslink through hydrogen bonds, thereby constructing a nacreous biomimetic brick-mud structure. After heat treatment, the modified ultrafiltration membrane is obtained.

[0042] As a further preferred embodiment, in step S1, the surface hydroxylation activation treatment includes: immersing the polyether ketone-based film in concentrated sulfuric acid and treating it at 20~30°C for 5-8 min to perform sulfonation and pore formation, and then transferring it to a NaBH4 / DMSO solution and reacting it at 120°C for 4 h under N2 protection to selectively reduce the ketone groups on the surface of the polyether ketone-based film to hydroxyl groups.

[0043] As a further preferred embodiment, in step S2, the buffer solution is a Tris-HCl buffer solution with a pH of 8.0-9.0; the concentration of dopamine is 1-5 g / L; and the oxidative self-polymerization reaction is carried out at 25-40°C in the dark for 6-24 h.

[0044] As a further preferred embodiment, in step S3, the molar ratio of phytic acid to zirconium ions is (1~3):1; the coordination pre-assembly is carried out at room temperature, and the pre-reaction time is 20~60 min; the immersion time of the PEK-OH / PDA composite membrane in the coordination complex solution is 1~4 h.

[0045] As a further preferred embodiment, in step S4, the polyethyleneimine is branched polyethyleneimine with a molecular weight of 10,000 to 70,000; the mass concentration of the polyethyleneimine solution is 1 to 5 wt%; the immersion time is 15 to 60 min; and the heat treatment temperature is 50 to 80°C for 1 to 4 h.

[0046] Example 3 This embodiment provides a method for treating high-sulfate mine water based on ettringite precipitation coupled with modified membrane separation. The modified ultrafiltration membrane described in Example 1 is used for solid-liquid separation. The method includes the following steps: A1: High-sulfate mine water is introduced into the ettringite reactor, and alkaline solution is added to adjust the pH to 10.5~12.5; A2: Add calcium aluminate powder to the ettringite reactor and react for 30-90 minutes under stirring to generate ettringite precipitate; A3: The reaction mixture containing calcite precipitate is fed into a membrane separation unit equipped with the modified ultrafiltration membrane, and solid-liquid separation is performed by cross-flow filtration. The permeate is collected as product water. A4: Adjust the pH of the produced water to neutral before reuse or discharge.

[0047] As a further preferred embodiment, in step A2, the dosage of calcium aluminate powder is 6.5~10.5 g / L, the stirring speed is 200~400 rpm, and the reaction temperature is 20~25°C; In step A3, the transmembrane pressure of the cross-flow filtration is 0.1~0.5 MPa, and the cross-flow velocity is 1.0~3.0 m / s; As a further preferred embodiment, when the transmembrane pressure difference rises to 1.5 times the initial value, a chemical cleaning procedure is initiated: first, the membrane is washed with 0.5~1.0 wt% NaOH solution for 30~60 min, then with 0.2~0.5 wt% HCl solution for 30~60 min, and finally rinsed with deionized water until neutral; the flux recovery rate of the modified ultrafiltration membrane after chemical cleaning is ≥86%.

[0048] As a further preferred embodiment, the solid-liquid separation time of the method is shortened from several hours of gravity sedimentation to minutes; the sulfate removal rate is ≥80%.

[0049] Example 4

[0050] I. Preparation of modified ultrafiltration membranes (e.g.) Figure 3 , Figure 4 (as shown) S1: PEK base film surface hydroxylation activation A 150 μm thick PEK membrane was immersed in 98 wt% concentrated sulfuric acid and treated at 25°C for 6 min to induce sulfonation and pore formation, creating a microporous structure on the membrane surface and introducing sulfonic acid groups. The membrane was then transferred to a NaBH4 / DMSO solution (NaBH4:DMSO = 1 mg:2 mL) and reacted at 120°C for 4 h under N2 protection, selectively reducing ketone groups (C=O) on the membrane surface to hydroxyl groups (-OH). After the reaction, the membrane was ultrasonically cleaned sequentially with methanol, deionized water, 0.1 M dilute hydrochloric acid, and anhydrous ethanol for 10 min each. Finally, it was dried in a vacuum oven at 60°C for 24 h to obtain a hydroxylated PEK membrane (denoted as PEK-OH).

[0051] S2: Polydopamine (PDA) Interlayer Deposition The PEK-OH membrane prepared in step S1 was immersed in a Tris-HCl buffer solution (10 mM, pH=8.5) containing 2 g / L dopamine hydrochloride and reacted at 30°C in the dark for 12 h to allow dopamine to undergo oxidative self-polymerization on the membrane surface. After the reaction, the membrane was rinsed three times with deionized water to remove unreacted monomers and physically adsorbed polydopamine particles, yielding the PEK-OH / PDA composite membrane. Characterization showed that the thickness of the PDA interlayer was approximately 20 nm.

[0052] S3: Phytic acid-zirconium ion coordination preassembly Phytic acid (50 wt% aqueous solution) was diluted to 10 wt% with deionized water and mixed with 0.05 M ZrOCl2·8H2O solution at a phytic acid:Zr ratio. 4+ The mixture was prepared at a molar ratio of 2:1 and pre-reacted at room temperature with magnetic stirring for 30 min to form a phytic acid-zirconium ion coordination complex (PA-Zr). 4+The PEK-OH / PDA composite membrane prepared in step S2 is immersed in the PA-Zr. 4+ In solution, the mixture was left to stand at 25°C for 2 hours to allow the coordination complex to anchor to the surface of the PDA intermediate layer through coordination, hydrogen bonding, and π-π stacking. After removal, the mixture was rinsed three times with deionized water.

[0053] S4: Polyethyleneimine hydrogen bonding crosslinking and nacre biomimetic assembly The membrane treated in step S3 was immersed in a 2 wt% aqueous solution of branched polyethyleneimine (PEI, Mw = 25,000) and reacted at 25°C for 30 min to allow the primary / secondary amine groups of PEI to form NH···O=P hydrogen bonds with the phosphate hydroxyl groups on the phytic acid molecules. After removal, the membrane was rinsed three times with deionized water, and finally heat-treated in a 60°C oven for 2 h to promote the full cross-linking and curing of the Zr-OP coordination bonds. After repeated rinsing with deionized water until neutral, and vacuum drying, a phytic acid-zirconium ion-polyethyleneimine modified PEK ultrafiltration membrane with a PDA interlayer (denoted as PEK-OH / PDA / PA-Zr) was obtained. 4+ -PEI film). Test characterization showed that the thickness of the phytic acid-zirconium ion-polyethyleneimine functional layer was approximately 100 nm.

[0054] II. Experiments on the treatment of high-sulfate mine water (e.g.) Figure 2 (As shown) The water quality parameters of high-mineralization mine water from a coal mine are as follows: SO4² - The concentration is 3850 mg / L, Ca² + The concentration was 1200 mg / L, and the pH was 7.8.

[0055] A1: Euclideanol reaction Mine water was introduced into the ettringite reactor, and 1 M NaOH solution was added to adjust the pH to 11.5. Calcium aluminate powder of type 3CaO·Al₂O₃ (e.g., ...) was added. Figure 1 The preparation process of calcium aluminate powder is shown below. The dosage of calcium aluminate powder is 8.5 g / L. The stirring speed is controlled at 300 rpm, the reaction temperature at 25°C, and the reaction time at 60 min. After the reaction is completed, samples are taken for analysis. The concentration of SO4²⁻ in the solution is [not specified]. - When the concentration decreased to 616 mg / L, the amount of ettringite precipitate formed was approximately 15.6 g / L.

[0056] A2: Modified membrane cross-flow filtration The mixture containing ettringite precipitate was fed into PEK-OH / PDA / PA-Zr. 4+The PEI-modified membrane separation unit operates using a cross-flow filtration method. The transmembrane pressure is set to 0.3 MPa, the operating temperature to 25°C, and the cross-flow velocity to 2.0 m / s. After 3 hours of continuous operation, when the transmembrane pressure difference rises to 1.5 times the initial value, a chemical cleaning procedure is initiated: first, an alkaline wash with 0.5 wt% NaOH solution for 30 min, followed by an acid wash with 0.2 wt% HCl solution for 30 min, and finally rinsing with deionized water until neutral.

[0057] The results showed that the initial water contact angle of the membrane was 28° and the initial membrane flux was 752 L·m. - ²·h - ¹, After 3 hours of operation, the membrane flux decreased to 529 L·m - ²·h - ¹, the flux decline rate was 29.6%. After chemical cleaning, the flux recovered to 647 L·m⁻¹. - ²·h - ¹, the recovery rate was 86%. SO4²⁻ in the product water - The concentration was 616 mg / L, and the total removal rate was 84%.

[0058] A3: pH adjustment of product water The permeate is sent to a high-density tank, and 0.5 M HCl solution is added to adjust the pH to 7.0. After meeting the standard, it is reused.

[0059] A4: Resource Utilization of Euclideanolite The retained ettringite precipitate is dehydrated to a moisture content of 55% using a plate and frame filter press, and then dried for resource utilization as a raw material for concrete expansion agent.

[0060] Example 5: Treatment effects of different calcium aluminate powder dosages Using the same mine water quality and modified ultrafiltration membrane as in Example 4, the dosage of calcium aluminate powder was varied to investigate the sulfate removal effect. The reaction pH was controlled at 11.5, the reaction time at 60 min, and other conditions were the same as in Example 4. The dosage of calcium aluminate powder (g / L) was controlled with gradients of 6.5, 7.5, 8.5, 9.5, and 10.5, while other conditions remained unchanged.

[0061] like Figure 5 As shown, the results indicate that when the dosage of calcium aluminate powder reaches 8.5 g / L, the sulfate removal rate is 84%. Increasing the dosage to above 9.5 g / L does not significantly improve the removal rate, but it increases reagent costs and sludge production. Therefore, the preferred dosage is 8.5 g / L.

[0062] Example 6: Treatment effect of different reaction pH Using the same mine water quality, modified ultrafiltration membrane, and calcium aluminate powder dosage (8.5 g / L) as in Example 4, the reaction pH was varied to investigate the sulfate removal effect and the stability of the modified membrane. pH gradients of 10.5, 11, 11.5, 12, and 12.5 were set, with other conditions remaining unchanged.

[0063] The results showed that the sulfate removal rate increased with increasing pH in the range of 10.5–12.5. The removal rate reached 88.9% at pH 11.5. The flux decline rate of the modified membrane was 20.8% after 2 hours at pH 11.5, indicating that PA-Zr… 4+ - The PEI modified layer exhibits good structural stability in a strongly alkaline environment.

[0064] Example 7 Different PA:Zr 4+ The effect of molar ratio During the preparation of the modified membrane, with other conditions kept constant, the PA:Zr ratio was set separately. 4+ The antifouling performance of the modified membranes in the ettringite system was investigated using molar ratios of 1:1, 2:1, and 3:1. The results showed that when the PA:Zr ratio was 1:1, 2:1, and 3:1, the antifouling performance of the membranes was significantly improved. 4+ At a molar ratio of 2:1, the modified membrane exhibited the lowest flux decay rate (30.0%) and the highest recovery rate (86.0%). At a molar ratio of 1:1, insufficient coordination crosslinking density led to an increase in flux decay rate to 38.5% and a decrease in recovery rate to 78.2%. At a molar ratio of 3:1, excessive phytic acid resulted in a porous coating, with a flux decay rate of 34.6% and a recovery rate of 81.5%. This indicates that the PA:Zr... 4+ =2:1 is the key parameter for achieving the best synergistic effect.

[0065] Example 8: Continuous Operation Test of Actual Mine Water Mine water quality: SO4² - 3200~6000 mg / L, Ca² + 980~1450 mg / L, pH 7.2~8.5.

[0066] Using the same process parameters as in Example 4 (reaction pH 11.5, calcium aluminate powder 8.5 g / L) and modified membrane, the chemical cleaning procedure was initiated when the transmembrane pressure difference rose to 1.5 times the initial value.

[0067] Results after 7 consecutive days of operation: The average sulfate removal rate was 80.5%. Membrane flux increased from the initial 752 L·m⁻¹. - ²·h -¹When the flux decreased slowly by 30%, chemical cleaning was performed, and the flux recovery rate after cleaning was >86%. No obvious ettringite scale layer was observed on the modified membrane surface, and there was no peeling or cracking. This proves that the modified membrane and process of the present invention are feasible for long-term stable operation under actual engineering conditions, and the sulfate removal rate can be stably controlled at over 80%.

[0068] The results show that the method of the present invention has a good removal effect on wastewater with high sulfate concentrations. By adjusting the dosage of calcium aluminate powder and the reaction pH, the sulfate removal rate can be stably controlled at over 80%, proving that the process has wide applicability and controllability.

[0069] Comparative Example 1: Treatment effect of unmodified PEK membrane Using the same mine water quality and treatment conditions as in Example 1, Only PEK-OH / PDA / PA-Zr 4+ - The PEI modified membrane was replaced with an unmodified PEK ultrafiltration membrane, and cross-flow filtration experiments were conducted.

[0070] The results showed that the initial water contact angle of the unmodified PEK membrane was 92° and the initial membrane flux was 325 L·m. - ²·h - ¹. After 2 hours of operation, obvious ettringite particles adhered to the membrane surface, and the transmembrane pressure difference increased sharply; after 3 hours of operation, the membrane flux decline rate reached 49.0%, and chemical cleaning only restored 56.5%. SO4² - The removal rate was only 42%. This indicates that the unmodified PEK membrane is extremely prone to severe fouling in high-concentration ettringite suspensions, with very poor sulfate removal performance, and cannot meet the requirements for continuous and stable operation.

[0071] Comparative Example 2: Preparation of Phytic Acid-Modified PEK Membrane (PA / PEK) This example provides a PEK membrane modified only with phytic acid. The preparation method is basically the same as in Example 4, except that the hydroxylated PEK membrane is treated with a 10 wt% phytic acid solution for 2 h, and then the PEI treatment is omitted, and heat treatment is performed directly. A PA / PEK membrane is obtained.

[0072] The results showed that, using the same mine water quality and treatment conditions as in Example 4, a cross-flow filtration experiment was conducted using a PA / PEK membrane, running continuously for 3 hours. The water contact angle of this membrane was 45°, and the initial membrane flux was 610 L·m⁻¹. - ²·h - ¹. After 3 hours of operation, the membrane flux decline rate reached 42.8%; after chemical cleaning, the recovery rate was 71.2%. The sulfate removal rate in the permeate was 68%.

[0073] Comparative Example 3 (with PDA intermediate layer but without PA-Zr)4+ -PEI functional layer) This comparative example provides a modified PEK membrane (PEK-OH / PDA membrane) containing only a PDA interlayer. The preparation method differs from Example 4 in that, after completing step S2 (PDA deposition), steps S3 and S4 (PA-Zr deposition) are not performed. 4+ Coordination pre-assembly and PEI crosslinking treatment, followed by direct drying, yields a PEK-OH / PDA membrane.

[0074] Cross-flow filtration experiments were conducted using the same mine water quality and treatment conditions as in Example 4. The results showed that the initial water contact angle of the PEK-OH / PDA membrane was 52°, and the initial membrane flux was 580 L·m⁻¹. - ²·h - ¹. After 3 hours of continuous operation, the membrane flux decreased to 342 L·m⁻¹. - ²·h - ¹, the flux decline rate was 41.0%; after chemical cleaning, the flux recovered to 435 L·m - ²·h - ¹, the recovery rate was 75.0%. SO₄²⁻ in the product water - The concentration was 1232 mg / L, and the sulfate removal rate was 68.0%.

[0075] The above results indicate that although the PDA intermediate layer alone possesses certain hydrophilicity and antifouling capabilities, its antifouling effect is far inferior to that of the PDA and PA-Zr combination in Example 4. 4+ - The synergistic combination of the PEI functional layer. Proof of the PDA intermediate layer and PA-Zr 4 + -There is a significant synergistic effect between the PEI functional layers, rather than a simple superposition.

[0076] Comparative Example 4 (including PDA intermediate layer but PA-Zr) 4+ (The coordination crosslinking does not contain zirconium ions) This comparative example provides a modified membrane (denoted as PEK-OH / PDA / PA-PEI membrane), the preparation method of which differs from that of Example 4 in that ZrOCl2 is not added in step S3, that is, only 10 wt% phytic acid solution is used to treat the PEK-OH / PDA composite membrane for 2 h, and the remaining steps are the same as those in Example 4.

[0077] Cross-flow filtration experiments were conducted using the same mine water quality and treatment conditions as in Example 4. The results showed that the initial water contact angle of the PEK-OH / PDA / PA-PEI membrane was 38°, and the initial membrane flux was 665 L·m⁻¹. - ²·h - ¹. After 3 hours of continuous operation, the membrane flux decreased to 419 L·m. - ²·h- ¹, the flux decline rate was 37.0%; after chemical cleaning, the flux recovered to 525 L·m - ²·h - ¹, the recovery rate was 78.9%. Test characterization showed that the functional layer on the membrane surface exhibited obvious cracks and localized detachment after operation.

[0078] The results showed that, compared with Example 4 (containing Zr), Comparative Example 4 without Zr had nearly twice the flux decay rate and a significantly lower recovery rate. This indicates that Zr... 4+ Coordination and crosslinking are key to constructing stable functional layers and achieving excellent antifouling performance. 4 + There is a specific synergistic effect between the PDA and the intermediate layer—the PDA provides anchor points to stabilize and fix the Zr-OP coordination network, while the rigidity of the Zr-OP network enhances the shear resistance of the functional layer.

[0079] Comparative Example 5: Comparison of the antifouling performance of modified membranes for different precipitation systems This comparative example uses the same PEK-OH / PDA / PA-Zr as Example 4. 4+ - PEI modified membrane and treatment process, but the precipitation system is replaced by: (A) calcium carbonate precipitation system; (B) magnesium hydroxide precipitation system; (C) calcium carbonate / magnesium hydroxide mixed precipitation system.

[0080] Experimental Group A (Calcium Carbonate System): Na₂CO₃ was added to the mine water to adjust the pH to 11.5, resulting in the formation of CaCO₃ precipitate. All other conditions were the same as in Example 4. Results showed that the initial membrane flux was 745 L·m⁻¹. - ²·h - ¹ After 3 hours of continuous operation, the flux decreased to 482 L·m - ²·h - ¹, the flux decline rate was 35.3%; after chemical cleaning, the flux recovered to 610 L·m - ²·h - ¹, the recovery rate was 81.9%.

[0081] Experimental Group B (Magnesium Hydroxide System): NaOH was added to the mine water to adjust the pH to 11.5, generating Mg(OH)₂ precipitate. All other conditions were the same as in Example 4. Results showed that the initial membrane flux was 738 L·m⁻¹. - ²·h - ¹ After 3 hours of continuous operation, the flux decreased to 468 L·m - ²·h - ¹, the flux decline rate was 36.6%; after chemical cleaning, the flux recovered to 598 L·m - ²·h -¹, the recovery rate was 81.0%.

[0082] Experimental Group C (calcium carbonate / magnesium hydroxide mixed system): Na₂CO₃ and NaOH were added to the mine water to adjust the pH to 11.5, simultaneously generating CaCO₃ and Mg(OH)₂ precipitates. Other conditions were the same as in Example 4. Results showed that the initial membrane flux was 740 L·m⁻¹. - ²·h - ¹ After 3 hours of continuous operation, the flux decreased to 450 L·m - ²·h - ¹, the flux decline rate was 39.2%; after chemical cleaning, the flux recovered to 585 L·m - ²·h - ¹, the recovery rate was 79.1%.

[0083] The above results demonstrate that the PEK-OH / PDA / PA-Zr of the present invention... 4+ - The flux decay rate of the PEI modified membrane in treating the ettringite precipitation system (29.6%) was lower than that in treating the calcium carbonate system (35.3%), the magnesium hydroxide system (36.6%), and the mixed system (39.2%), by 5.7, 7.0, and 9.6 percentage points, respectively; the chemical cleaning recovery rate (86%) was higher than that of other systems (81.9%, 81.0%, and 79.1%), by 4.1, 5, and 6.9 percentage points, respectively.

[0084] Conclusion: The three-layer gradient modified membrane (PEK-OH / PDA / PA-Zr) containing a PDA intermediate layer in Example 4 of this invention... 4+ -PEI) exhibited the best antifouling performance among all membranes: the lowest flux decline rate (29.6%) and the highest chemical cleaning recovery rate (86%), while also achieving a high sulfate removal rate (84%). This fully demonstrates the effectiveness of the introduction of the PDA interlayer in PA-Zr 4+ - A significant synergistic effect was generated between the PEI functional layers: the catechin groups of PDA formed covalent bonds with PEK-OH, providing a strong anchor for the functional layers; the aromatic rings of PDA and phytic acid formed π-π stacking, enhancing interfacial bonding; the catechin groups of PDA enhanced the Ca²⁺ ionotropic effect on the surface of ettringite particles. + The specific chelation generates active electrostatic repulsion. The three elements work synergistically, resulting in overall antifouling performance far exceeding that of products without a PDA interlayer, functional layer, or Zr. 4+ The proportions of each pair.

[0085] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A modified ultrafiltration membrane for solid-liquid separation in systems containing suspended particles, characterized in that, The modified ultrafiltration membrane comprises, in sequence, a polyetherketone-based membrane, a polydopamine interlayer, and a phytic acid-zirconium ion-polyethyleneimine functional layer; the polydopamine interlayer is composited on the surface of the polyetherketone-based membrane, and the phytic acid-zirconium ion-polyethyleneimine functional layer is composited on the surface of the polydopamine interlayer. The phytic acid-zirconium ion-polyethyleneimine functional layer has a nacreous biomimetic structure formed by the interpenetration of an inorganic framework formed by the coordination and cross-linking of phytic acid and zirconium ions and an organic network formed by the cross-linking of polyethyleneimine through hydrogen bonds.

2. The modified ultrafiltration membrane according to claim 1, characterized in that, The modified ultrafiltration membrane has a water contact angle of 25-35° on its surface and is structurally stable in a strongly alkaline environment with a pH of 10.5-12.

5.

3. The modified ultrafiltration membrane according to claim 1, characterized in that, The thickness of the polyetherketone-based film is 100-250 μm; the thickness of the polydopamine interlayer is 5-50 nm; and the thickness of the phytic acid-zirconium ion-polyethyleneimine functional layer is 50-200 nm. Preferably, the surface of the polyetherketone-based film is subjected to surface hydroxylation activation treatment to form a surface-hydroxylated polyetherketone-based film; Preferably, the molar ratio of phytic acid, zirconium ions and polyethyleneimine in the phytic acid-zirconium ion-polyethyleneimine functional layer is (1-3):1:(0.5-6).

4. The modified ultrafiltration membrane according to claim 1, characterized in that, When the modified ultrafiltration membrane is used for cross-flow filtration, the flux recovery rate after chemical cleaning is ≥86%.

5. A method for preparing a modified ultrafiltration membrane for solid-liquid separation of a system containing suspended particles according to any one of claims 1-4, characterized in that, Includes the following steps: S1: The polyetherketone-based membrane is selectively reduced and activated with sodium borohydride to obtain a hydroxylated polyetherketone-based membrane; S2: The hydroxylated polyetherketone-based membrane prepared in step S1 is immersed in a buffer solution containing dopamine and subjected to an oxidative self-polymerization reaction under alkaline conditions to form a polydopamine intermediate layer on the surface of the hydroxylated polyetherketone-based membrane, thereby obtaining a PEK-OH / PDA composite membrane. S3: Phytic acid and zirconium ions are pre-assembled to form a phytic acid-zirconium ion coordination complex solution; the PEK-OH / PDA composite membrane prepared in step S2 is immersed in the coordination complex solution, so that the coordination complex is anchored on the surface of the polydopamine intermediate layer. S4: Immerse the membrane treated in step S3 into a polyethyleneimine solution to allow polyethyleneimine and phytic acid to crosslink through hydrogen bonds, thereby constructing a nacreous biomimetic brick-mud structure. After heat treatment, the modified ultrafiltration membrane is obtained.

6. The preparation method according to claim 5, characterized in that, In step S1, the surface hydroxylation activation treatment includes: immersing the polyether ketone-based film in concentrated sulfuric acid and treating it at 20~30°C for 5-8 min to perform sulfonation and pore formation, and then transferring it to NaBH4 / DMSO solution and reacting it at 120°C for 4 h under N2 protection to selectively reduce the ketone groups on the surface of the polyether ketone-based film to hydroxyl groups; Preferably, in step S2, the buffer solution is a Tris-HCl buffer solution with a pH of 8.0-9.0; the concentration of dopamine is 1-5 g / L; and the oxidative self-polymerization reaction is carried out at 25-40°C in the dark for 6-24 h. Preferably, in step S3, the molar ratio of phytic acid to zirconium ions is (1~3):1; the coordination pre-assembly is carried out at room temperature, and the pre-reaction time is 20~60 min; the PEK-OH / PDA composite membrane is immersed in the coordination complex solution for 1~4 h. Preferably, in step S4, the polyethyleneimine is branched polyethyleneimine with a molecular weight of 10,000 to 70,000; the mass concentration of the polyethyleneimine solution is 1 to 5 wt%; the immersion time is 15 to 60 min; and the heat treatment temperature is 50 to 80°C for 1 to 4 h.

7. A method for treating high-sulfate mine water based on ettringite precipitation coupled with modified membrane separation, characterized in that, Solid-liquid separation is performed using a modified ultrafiltration membrane as described in any one of claims 1-4, the method comprising the following steps: A1: High-sulfate mine water is introduced into the ettringite reactor, and alkaline solution is added to adjust the pH to 10.5~12.5; A2: Add calcium aluminate powder to the ettringite reactor and react for 30-90 minutes under stirring to generate ettringite precipitate; A3: The reaction mixture containing calcite precipitate is fed into a membrane separation unit equipped with the modified ultrafiltration membrane, and solid-liquid separation is performed by cross-flow filtration. The permeate is collected as product water. A4: Adjust the pH of the produced water to neutral before reuse or discharge.

8. The method according to claim 7, characterized in that, In step A2, the dosage of calcium aluminate powder is 6.5~10.5 g / L, the stirring speed is 200~400 rpm, and the reaction temperature is 20~25°C. In step A3, the transmembrane pressure of the cross-flow filtration is 0.1~0.5 MPa, and the cross-flow velocity is 1.0~3.0 m / s.

9. The method according to claim 8, characterized in that, When the transmembrane pressure difference rises to 1.5 times the initial value, the chemical cleaning procedure is initiated: first, wash with 0.5~1.0 wt% NaOH solution for 30~60 min, then wash with 0.2~0.5 wt% HCl solution for 30~60 min, and finally rinse with deionized water until neutral; the flux recovery rate of the modified ultrafiltration membrane after chemical cleaning is ≥86%.

10. The method according to claim 7, characterized in that, The solid-liquid separation time of the method is reduced from several hours by gravity sedimentation to minutes; the sulfate removal rate is ≥80%.

Citation Information

Patent Citations

  • Method for removing sulphate, calcium and / or other soluble metals from waste water

    CN104603068A

  • Sulfate radical removal precipitant recycling method

    CN108793498A

  • Pretreatment system and method for wastewater with high calcium sulfate mineralization degree

    CN109179743A